Pharmacogenetic Practice of Anticancer Drugs: Multiple Approaches for an Accurate and Comprehensive Genotyping - Montrasio C; Cheli S; Clementi E (Dove Medical Press, 2023)
Cristina Montrasio,1 Stefania Cheli,1 Emilio Clementi2,3 1Unit of Clinical Pharmacology, ASST Fatebenefratelli Sacco, L. Sacco University Hospital, Milan, Italy; 2Clinical Pharmacology Unit, Department of Biomedical and Clinical Sciences, L. Sacco University Hospital, Università degli Studi di Milano, Milan, Italy; 3Scientific Institute IRCCS Eugenio Medea, Bosisio Parini, ItalyCorrespondence: Cristina Montrasio, Unit of Clinical Pharmacology, Department of Laboratory Medicine, ASST Fatebenefratelli-Sacco, Milan, Italy, Email cristina.montrasio@asst-fbf-sacco.itAbstract: The application of pharmacogenetics in oncology is part of the routine clinical practice. In particular, genotyping of dihydropyrimidine dehydrogenase (DPYD) and UDP-glucuronosyltransferase (UGT1A1) is crucial to manage the treatment of patients taking fluoropyrimidines and irinotecan. The unique approach of our laboratory to the pharmacogenetic diagnostic service in oncology is to combine two real-time PCR methods, LightSNiP assay (TIB MOLBIOL), and more recently FRET (Fluorescent Resonance Energy Transfer) probes technology (Nuclear Laser Medicine), plus TaqMan assay (Thermo Fisher) for the confirmation of the presence of variant alleles on DNA from a second extraction. We found that both the FRET and LightSNiP assays, where detection occurs by melting curve analysis, offer an advantage over the competing TaqMan technology. Whereas unexpected genetic variants may be missed using a mutation-specific TaqMan assay, the information thus obtained can be useful to adjust the therapy in case of unexpected post-treatment toxicity. The combination of TaqMan and FRET assays helped us to achieve more accurate genotyping and a correct result for the patient. The added value of the DPYD FRET assay is the possibility of detecting, with the same amplification profile of the polymorphisms detailed in the guidelines, also the c.2194G>A (*6 rs1801160), cited in the recommendations as a variant to be investigated in case of severe toxicity. Regarding the UGT1A1 (TA)n promoter polymorphism (rs3064744), the distinctive and positive feature of the FRET assay is to allow clearly identifying all those potential variant alleles, including the (TA)5 and (TA)8 alleles, that are frequent in African Americans. Our clinical practice emphasizes the importance of not only rapid and easy-to-use assays, such as the new FRET ones, but also of accurate and comprehensive genotyping for good pharmacogenetic diagnostic activity.Keywords: real-time PCR, melting curve analysis, DPYD, UGT1A1, pharmacogenetics